Electrical Characteristics And Thermal Diffusivity Of Polypyrrole-Based Conducting Polymer - Othman, Norfazlinayati (2010)

(untitled)
Conducting polymer materials based on Polypyrrole (PPy) and Polypyrrole/Montmorillonite (PPy/MMT) clay composite were synthesis by using chemical reaction process with iron (III) chloride (FeCl3) as oxidizing and dopant agent. During the mixing process of PPy, the solution changed from transparent to dark green indicating that the polymerization process took place instantaneously. The resulting powder was filtered, washed, grounded and press into pellet. The structural, thermal and electrical properties of the conducting polymer and conducting polymer composite were then investigated. The structure of the samples was analyzed by using X-ray diffractometer (XRD) with the scanning was carried out at 2θ of 15° to 35° for doped PPy and at 2θ of 2° to 35° for PPy/MMT clay composite. The XRD spectra showed dopant and filler effect with appearance of broad peak at around the 2θ value of 25 to 26° corresponded to highly disordered parts and new peak at low angle at around the 2θ value of 5 to 6° corresponded to successfully intercalation of PPy chain in the galleries of MMT clay. It was observed that all the peak angles shifted and the full width at half maximum (FWHM) values are difference with increasing in dopant concentrations and filler percentages indicate the strong interaction between dopant and filler with the conjugated polymer. The interchain separation showed good agreement with published data.